2018
DOI: 10.5599/jese.478
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the cerium oxide primer layers deposited on AA2024-T3 aircraft alloy by preliminary Enhancement of the cerium oxide primer layers deposited on AA2024-T3 aircraft alloy by preliminary anodization

Abstract: <p class="PaperAbstract"><span lang="EN-US">The possibility for combination between Anodized Aluminum Oxide (AAO) and Cerium Oxide Primer Layer (CeOPL) for elaboration of efficient protective coatings for AA2024-T3 aircraft alloy is proposed in the present research. The combined AAO/CeOPL coating characterizations include Electrochemical Impedance Spectroscopy (EIS) combined with Linear Voltammetry (LVA), for extended times (until 2520 hours) to a model corrosive medium (3.5% NaCl). Topographical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this context, Arunnellaiappan et al [162] propose the formation of combined AAO/CeCC layers by applying PEO, combined with simultaneous electrophoresis of CeO 2 nanoparticles. Furthermore, the synergism between the CeCC layer and AAO sublayer, obtained under conventional conditions, was established by Andreeva et al [163], Kozhukharov et al [164], and confirmed by L. Selegård et al [165] and Ramirez et al [166].…”
Section: Application Of Cerium Oxide and Soluble Salts-based Material...mentioning
confidence: 78%
“…In this context, Arunnellaiappan et al [162] propose the formation of combined AAO/CeCC layers by applying PEO, combined with simultaneous electrophoresis of CeO 2 nanoparticles. Furthermore, the synergism between the CeCC layer and AAO sublayer, obtained under conventional conditions, was established by Andreeva et al [163], Kozhukharov et al [164], and confirmed by L. Selegård et al [165] and Ramirez et al [166].…”
Section: Application Of Cerium Oxide and Soluble Salts-based Material...mentioning
confidence: 78%
“…Twelve samples cut from the AA2024-T3 aircraft alloy were subjected to three subsequent coating procedures in order to acquire identical Al 2 O 3 /CeCC double-layer coatings with similar features to those described in an earlier work [41]. The coating procedures and the respective conditions are shown in Table 1.…”
Section: Experimental Sample Preparation and Treatmentmentioning
confidence: 99%
“…The acquired data underwent statistical treatment in order to obtain the respective confidential ranges of the measured values. The statistical data treatment approach is well-described and illustrated in previous works [41,44,45]. In order to collect sufficient data, each measurement was performed twice, so that eight results were acquired for each set of samples.…”
Section: Initial Surface Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation